Four monomeric copper(ii) complexes of non-steroidal anti-inflammatory drug Ibuprofen and N-donor ligands: syntheses, characterization, crystal structures and cytotoxicity studies. (17th July 2017) - Kumar, Santosh; Garg, Shipra; Sharma, Raj Pal; Venugopalan, Paloth; Tenti, Lorenzo; Ferretti, Valeria; Nivelle, Laetitia; Tarpin, Michel; Guillon, Emmanuel
Abstract : The cytotoxic effects of four new Ibuprofen–Cu(ii ) complexes were tested finding significant cytotoxicity on human melanoma cell line HT-144. Abstract : Reaction of hydrated copper(ii ) ibuprofenate with various nitrogen donor ligands, β-picoline, γ-picoline, pyrrolidine and unsymetrical dimethyl ethylenediamine (unsym-dmen), at room temperature in a methanol : water mixture (4 : 1 v/v) yielded four new complexes, [Cu(Ibu)2 (β-picoline)2 (H2 O)], 1 ; [Cu(Ibu)2 (γ-picoline)2 (H2 O)]·H2 O, 2 ; [Cu(Ibu)2 (pyrrolidine)2 ]·H2 O, 3; and [Cu(unsym-dmen)2 (H2 O)](Ibu)2, 4, respectively, where Ibu = deprotonated Ibuprofen (HIbu). The newly synthesized complexes have been characterized by elemental analyses, spectroscopic methods (FT-IR, UV-Vis and EPR), TGA and single crystal X-ray structure determination. Crystallographic investigations revealed that all the complexes are monomeric in nature, in contrast to the dimeric nature of copper(ii ) ibuprofenate solvates. EPR studies clearly revealed that the chromophore present in all complexes (1–4 ) is consistent with the structures determined by X-ray crystallography. The cytotoxic effects of all complexes were tested by a colorimetric assay on three human cell lines; though the activity was affected by the nature of the cell line, the newly synthesized complexes1–4 showed higher cytotoxicity than the parent molecule against all the tumoral cell lines.